Effects of ultrasonic cavitation on neutralization process of low molecular weight polyethylene glycol - Azarpour, A. (2019)
In recent decades, ultrasound has been broadly employed in different applications, particularly in the chemical industry. Ultrasound enhances chemical reactions in a solution via generation of cavitation microbubbles. It improves mass transfer rate and kinetic rate of targeted systems under various process conditions. In polyethylene glycol (PEG) production, the neutralization reaction is generally carried out by employing a mechanical stirring operation. However, this process produces a soluble salt containing potassium and acetate ions, which are known to appreciably manipulate/alter the properties of PEG. In this paper, ultrasound influence is initially analyzed through the neutralization of deionized water. This study then focuses on the neutralization of PEG using ultrasonic cavitation and its impact on the properties of PEG. The ultrasonic cavitation unit employed in this research is a COLE-ParmerÂ® 500 W & 20 kHz with an ultrasonic probe. To investigate the efficiency of the ultrasonic cavitation reactor and analyze the important aspects of the implemented method, the concentration of soluble salts and conductivity of PEG neutralized by the ultrasonic cavitation method are measured and compared with those of the commercial PEG prepared by the mechanical stirring methodology. The results reveal that the neutralization reaction via the ultrasonic cavitation lowers the conductivity and concentrations of potassium and acetate ions, compared to the traditional stirring methods. It is also concluded that the minimum conductivity and the minimum content of potassium and acetate ions are achieved at 30 power and a reaction time of 5 min. This study promises the efficient utilization of the ultrasonic cavitation in the industrial sectors, particularly in pharmaceutical industries. Â© 2018 Canadian Society for Chemical Engineering